Fibronectin enhances tumor metastasis through B7‐H3 in clear cell renal cell carcinoma. Issue 11 (3rd October 2021) - Xie, Jinjing; Sun, Meiyun; Zhang, Dongze; Chen, Chunyang; Lin, Simin; Zhang, Guangbo
Abstract : B7 homolog 3 (B7‐H3) plays an important role in tumor biology, but the molecular mechanism underlying the role of B7‐H3 in tumor metastasis remains unclear. In this article, our analysis of The Cancer Genome Atlas database suggested that B7‐H3 expression is associated with poor prognosis of patients with clear cell renal cell carcinoma (ccRCC). B7‐H3 knockdown affected the expression of metastasis‐related genes and significantly suppressed the metastasis of ccRCC cells, but it had no significant effect on the proliferation of ccRCC cells. Database analysis revealed a strong positive correlation between B7‐H3 and fibronectin (FN) in ccRCC cells, and further study also confirmed that FN interacts with B7‐H3. Silencing FN expression inhibited the migration and invasion of ccRCC cells, whereas exogenous FN promoted the migration and invasion of ccRCC cells, which was accompanied by activation of kinases [namely, phosphorylated (p)‐phosphoinositide 3‐kinase, p‐protein kinase B, p‐p38 and p‐extracellular regulated protein kinase]. B7‐H3 knockdown abolished the prometastatic effect of FN. In conclusion, our data suggest that B7‐H3 binds to exogenous FN and promotes the metastasis of ccRCC cells. Abstract : In this study, we explored the clinical significance and prognostic relationship of B7 homolog 3 (B7‐H3) in clear cell renal cell carcinoma (ccRCC). We report the novel discovery that B7‐H3 interacts with plasma fibronectin in promoting ccRCC metastasis. Cotargeting fibronectin and B7‐H3 may have potential as a new therapeutic intervention strategy for ccRCC treatment.